ЭЛЕКТРОМАГНИТНЫЕ ПРОЦЕССЫ В КАБЕЛЬНОЙ ЛИНИИ С ПОЛИЭТИЛЕНОВОЙ ИЗОЛЯЦИЕЙ НА НАПРЯЖЕНИЕ 330 кВ - Щерба, А.А.; Подольцев, А.Д.; Кучерявая, И.Н. (Інститут електродинаміки НАН України, Київ, 2012)
In computing environment of Matlab/Simulink, the software for modeling of transient electromagnetic processes in high-powered energy system that contains extra-high voltage (330 kV) cable line with cross-linked polyethylene insulation is developed. The working conditions of single-phase and three-phase sort circuit in the cable line as well as the overvoltages in cable screens that take place in screen transposition nodes are studied. References 6, figures 11.